Effects of roughage and protein levels on performance of finishing steers and heifers - Harrison, K.F.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
A 142-day trial used 36 Angus steers and 63 mixed-breed heifers to study the effects of roughage and protein levels in beef cattle finishing rations. Results from a 13% crude protein ration the first 70 days or a ration with supplemental protein removed the final 30 days did not differ significantly from results with an 11% crude protein ration. Rations containing 10.0, 17.5 or 25.0% roughage (dry matter basis) made no significant difference in performances by steers or heifers.
Keywords: Beef; Roughage; Protein; Performance; Steers; Heifers